2018
DOI: 10.21769/bioprotoc.2467
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo Whole-cell Recordings in Adult Drosophila Brain

Abstract: Cost-effective and efficient, the fruit fly (Drosophila melanogaster) has been used to make many key discoveries in the field of neuroscience and to model a number of neurological disorders. Great strides in understanding have been made using sophisticated molecular genetic tools and behavioral assays. Functional analysis of neural activity was initially limited to the neuromuscular junction (NMJ) and in the central nervous system (CNS) of embryos and larvae. Elucidating the cellular mechanisms underlying neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Though the site of seizure generation in flies is unknown, LNs in the fly antennal lobes are a readily accessible population of GABAergic inhibitory neurons in the important and well characterized olfactory circuit within the Drosophila brain ( Seki et al, 2010 ). To observe neuronal firing and sodium channel activity in these neurons, the whole brain was dissected out of adult flies ( Roemmich et al, 2018 ), dorsal lateral local neurons were identified by their location and morphology, and whole-cell electrophysiological recordings were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the site of seizure generation in flies is unknown, LNs in the fly antennal lobes are a readily accessible population of GABAergic inhibitory neurons in the important and well characterized olfactory circuit within the Drosophila brain ( Seki et al, 2010 ). To observe neuronal firing and sodium channel activity in these neurons, the whole brain was dissected out of adult flies ( Roemmich et al, 2018 ), dorsal lateral local neurons were identified by their location and morphology, and whole-cell electrophysiological recordings were performed.…”
Section: Resultsmentioning
confidence: 99%
“…al., 2010). To observe neuronal firing and sodium channel activity in these neurons, the whole brain was dissected out of adult flies (Roemmich et. al., 2018), dorsal lateral local neurons were identified by their location and morphology, and whole-cell electrophysiological recordings were performed.…”
Section: R1648h Inhibitory Neuronsmentioning
confidence: 99%
“…While we have yet to observe positive results in any epilepsy candidate genes, these methods can provide a strong tool for studying genes involved in synaptic function coding in epilepsy. Combining these electrophysiological methods with the LPF recording technique in the CNS of Drosophila ( Iyengar and Wu, 2021 ) can develop an instrumental platform for investigating the cellular and synaptic mechanisms underlying neural function or dysfunction ( Roemmich et al, 2018 ), with excellent accessibility for studying epilepsy’s pathological and pharmacological aspects ( Sheeba et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flies have also become convenient models to perform neuronal cell recording in the adult brain (ex vivo) that can be studies in the context of genetic and/or pharmacological manipulations (Gu and O'dowd, 2007;Roemmich et al, 2018). As an example, electrophysiological studies carried out in adult flies that were genetically modified to mimic DS were pioneers in showing the link between pathological missense mutations and disturbances of sodium ion current activity at the receptor level (Sun et al, 2012;Schutte et al, 2014).…”
Section: From Gene Mutation To Brain Network Perturbation (Temporal Mmentioning
confidence: 99%